Efeito do treinamento resistido na avaliação da composição corporal e na atividade da MMP-2 nos músculos bíceps e gastrocnêmio de ratos obesos - Souza, Markus Vinicius Campos (Universidade Federal de São Carlos, 2013)
The aim of the present study was to investigate the influence of resistance training on body composition and active matrix metalloproteinases 2 (MMP-2) on biceps and gastrocnemius muscles in rats with high fat diet. We evaluated 32 Wistar rats divided into four experimental groups (n=8/each) according to diet and exercise status: Control Group (C; standard diet), Obese Control Group [C-Ob; hiperlipidic diet (30% of fat)], Resistance Exercise (RE; standard diet) and Resistance Exercise Obese (RE-Ob; hiperlipidic diet). After weaning (day 21), animals were subjected to the experimental diet according to their groups during 24 weeks. A 12-week strength-training period was used, during which the animals climbed a 1.1-m vertical ladder with weights attached to their tails. The sessions were performed three times/week (Mondays, Wednesdays and Fridays, with 4 9 climbs/session and 8 12 dynamic movements/climb with two rest minutes. Resistance training induced a significant reduction in body mass, fat mass, fat percentage in group RE (p < 0,05). Resistance training increased the activity of MMP-2 on bicpes and gastrocnemius muscle (p < 0,05), favoring thus the tissue remodeling in both groups trained. Finally, the carrying load trained both groups was not statistically different, however, the relative strength (carrying load/body weight) was statistically higher in group RE (p < 0,05). Resistance training promoted significant changes in body composition, MMP-2 activity in the biceps and gastrocnemius and the relative strength. Thus resistance training may be a strategy to minimize the deleterious effects induced by consumption of a high fat diet and the co-morbidities associated with obesity in skeletal muscle.
Keywords: Fisiologia; Treinamento Resistido; Obesidade; Metaloproteinase (MMP-2); Musculo Esquelético; Resistance Training; Obesity; Matrix Metalloproteinases 2 (MMP-2); Skeletal Muscle; CIENCIAS BIOLOGICAS::FISIOLOGIA